The Emancipation of Women and Right to Abortion in USSR on the Example of Andrei Platonov’s Play Fools on the Periphery (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper discusses the influence of the Soviet government on creating the “new Soviet woman,” who is meant to respond to the ideological needs of the new social arrangement, and the government’s subsequent attitude towards her, on the example of Andrei Platonov’s play Fools on the Periphery. The emancipation of women, their inclusion in all spheres of life, as well as their right to abortion are, as it turns out, only the government’s mechanisms, created to establish an absolutist regime and have no contact with the aspiration of socialism to improve the lives of women both in the province and in the capital. The new emancipated Soviet woman in the 1920s and 1930s gained fictitious rights that led to social catastrophe. Looking for their place in socialism, women were torn between hard work and domestic responsibilities, which further threatened their former position. By all accounts, socialist women are equal to men in terms of the right to work, while in other spheres, they are further humiliated (maternity, salary, type of work place etc.). All described phenomena can be noticed on the example of Platonov’s drama, in the character of the former housewife Marya Basmakova, who loses her own identity in the process of the so-called Soviet emancipation. Even though Marya Basmakova herself is not aware of her rights and ways of enforcing them, it becomes obvious to her that all the new changes do not represent a path to women’s liberation, but lead to complete control over women’s bodies, pregnancy and abortion. The death of her child symbolises the collapse of a false project of women’s emancipation in which her character represents the dead foundation on which the image of a progressive Soviet government was built.
Keywords: abortion; social policy of the USSR; women’s emancipation; OHMATMLAD commission